(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
Together with the challenge of teaching and transmitting knowledge about plants, the 1st Day of Botany was held with students, the team working at the Magé semi-presencial polo (CEDERJ/UAB) and the community around the polo with the objective of promoting extension, scientific dissemination and teaching. The objective of this work is to offer considerations about extension and reverberations from this academic event. With this we test the following hypotheses and (i) the agents involved in this event have improved the engagement and development of individual capacities. (ii) the event evidences the Magé pole as a space of multifunctionality within the municipality. The methodological paths were of the qualitative type with direct and indirect observations that were carried out in the actions before, during and after the botany day event. All these actions were recorded in a field notebook. There was also a quantitative analysis of the ones with control forms and registration of all the participants and an evaluation questionnaire of the event for the listening public. The various participants of the event were engaged and developed individual capabilities, and the event reinforces the Magé pole as a multifunctional space within the municipality. The teaching and extension of plants had dialogical interaction and reinforced intrinsic factors of motivation, which helped some participants in sensitive issues that go through the evasion of EaD. Part of the success of the event was in the protagonism of students and agents of the pole, making a change of polarization in face of events traditionally offered, not being institutional receivers. Extension events of this nature in semi-presential poles should be replicated and stimulated to improve EaD courses in Brazil. Keywords: Extension in EaD; Ethnobotany; Botany Day. Science teaching.